2012
DOI: 10.1021/cs3004227
|View full text |Cite
|
Sign up to set email alerts
|

Correlating Ethylene Glycol Reforming Activity with In Situ EXAFS Detection of Ni Segregation in Supported NiPt Bimetallic Catalysts

Abstract: The structural changes in supported NiPt/C and NiPt/γ-Al2O3 catalysts were investigated using in situ extended X-ray absorption fine structure (EXAFS) under aqueous phase reforming (APR) of ethylene glycol conditions. Reverse Monte Carlo is introduced to analyze the EXAFS data. Parallel reactor studies of APR of ethylene glycol showed that NiPt catalysts were initially more active than monometallic Pt catalysts. The enhanced activity was correlated to changes in the catalyst structure. Under APR conditions, Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
69
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 42 publications
7
69
0
Order By: Relevance
“…One of the critical questions in correlating UHV surface‐science results with supported catalysts is the stability of the catalysts under the reaction conditions. In situ extended X‐ray absorption fine structure (EXAFS) studies have been performed to determine the stability of carbon‐supported bimetallic catalysts (NiPt/C) under aqueous‐phase‐reforming (APR) conditions 92b. The magnitude of k 2 ‐weighted EXAFS Pt L 3 ‐edge spectra for NiPt/C under reductive (10 % H 2 ) and under ethylene glycol APR conditions are shown in Figure 5.…”
Section: Selective Cc Bond Scission: Reforming Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the critical questions in correlating UHV surface‐science results with supported catalysts is the stability of the catalysts under the reaction conditions. In situ extended X‐ray absorption fine structure (EXAFS) studies have been performed to determine the stability of carbon‐supported bimetallic catalysts (NiPt/C) under aqueous‐phase‐reforming (APR) conditions 92b. The magnitude of k 2 ‐weighted EXAFS Pt L 3 ‐edge spectra for NiPt/C under reductive (10 % H 2 ) and under ethylene glycol APR conditions are shown in Figure 5.…”
Section: Selective Cc Bond Scission: Reforming Reactionsmentioning
confidence: 99%
“…For the reduced catalyst, a small PtPt coordination number and a relatively larger PtNi coordination number coupled with a short PtNi bond (2.53 Å) all suggested that the NiPt nanoparticles formed a core–shell structure with the core rich in Ni and the shell rich in Pt. Under APR conditions, the NiPt nanoparticles underwent restructuring, confirming the qualitative observations from Figure 5; atomistic‐reconstruction simulation results are shown visually in Table 3 92b. Under APR conditions, Pt atoms diffused to the core of the nanoparticles whereas Ni segregated to the surface.…”
Section: Selective Cc Bond Scission: Reforming Reactionsmentioning
confidence: 99%
“…4 However, a number of studies have observed that the surface composition of bimetallic catalysts depends on the reaction environment 5−8 with implications for catalytic activity; for example, Niterminated NiPt particles are more active for aqueous-phase reforming. 9 Furfural is another biomass-derived molecule that, like anisole and guaiacol, has attracted attention due to its potential use as a fuel precursor, and has been used as a probe for understanding the reactivity of complex oxygenates. Furfural hydrogenation and hydrodeoxygenation over precious metal catalysts has been investigated in a number of studies.…”
mentioning
confidence: 99%
“…This biomass‐based resource that can be readily made from sugars and cellulose has gained popularity for H 2 production via reforming . Over the years, several reports on H 2 production via steam, aqueous and auto‐thermal reforming of EG have been published . Unfortunately, these existing processes suffer from drawbacks like limited H 2 concentrations, harsh operating conditions, severe coke deposition and high energy costs ,,…”
Section: Introductionmentioning
confidence: 99%